THEORETICAL FOUNDATIONS AND PECULIARITIES OF THE VARIABILITY OF SOCIAL STRATIFICATION PROCESSES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Today, the main goal of all nations and peoples of the world is peaceful life and well-being.If we analyze the structure of society in human life, we see that it is based on religious, ethnic, class, demographic, territorial units.The article analyzes the fact that people living in society in one way or another cause social inequality by social status, occupation, demographic characteristics and belonging to different social groups.